A new bunion shoe design using geometric analysis hallux valgus angle (HVA) for Malaysian women - Dayang Intan Farahanies AlMurid (Tanjong Malim, 2022)
A new bunion shoe design using geometric analysis hallux valgus angle (HVA) for Malaysian women by Dayang Intan Farahanies AlMurid